Martial arts fun - Meister, Cari (2021)
"Martial Arts are thrilling to watch, but they're even more fun to do! Kids can take part in the sport by learning what martial arts are, what gear and skills are needed, what happens during lessons, and how to be a good sport. A skill-building activity helps kids participate in the fun"--
What are martial arts? -- What do I need to do martial arts? -- Where do I train for martial arts? -- How do I train for martial arts? -- How can I be a good sport? -- Skill builder: go the distance.
Includes bibliographical references and index.
Ages 6-8
Grades 2-3
Keywords: Martial arts -- Juvenile literature